PENGARUH TENAGA KERJA, TEKNOLOGI DAN PENGALAMAN BERTANI TERHADAP PRODUKTIVITAS PETANI DENGAN PELATIHAN SEBAGAI VARIABEL MODERATING - Sugiantara, I Gusti Ngurah Made; Utama, Made Suyana (Buletin Studi Ekonomi, 2019)
Abstract: Effect of Labor, Technology and Farming Experience on Productivity of Farmers with Training as Moderating Variables. This study aims to analyze the effect of simultaneous and partial labor, technology, farming experience, training and interaction of labor and training on the productivity of asparagus farmers in the District of Badung. The data used are primary data, the population is all asparagus farmers. The number of samples was 93 farmers, the sample was determined by the proportionate stratified random sampling method. The data analysis technique is multiple linear regression with moderating variables. Based on the results of the analysis found simultaneously the variables of labor, technology, farming experience, training and interaction of labor and training affect the productivity of farmers. Partially the variables of labor, technology and farming experience have a positive and significant effect on farmer productivity, while partially training does not have a positive and significant effect on farmer productivity. Training is a moderating variable for the effect of labor on the productivity of asparagus farmers in Petang District, Badung Regency.